Socialization On Improving The Quality Of Coffee Beans For Residents Of Muara Betung Village, Ulu Musi Sub-District District Four Lawang - Putri, Cyndi Dwi; Trisnawati, Novika; Gibran, Ahmad; Kurniawan, Aditia; Putra, Iklas Ade; Utama, Gilang Fajar; Effendi, Yanto; Soleh, Ahmad; Gayatri, Ida Ayu Made Er Meytha (Jurnal Pengabdian Mandiri, 2025)
The socialization activity to improve the quality of coffee beans of Desa Muara Betung Kecamatan Ulu Musi Kabupaten Empat Lawang. Was carried out to improve the community's understanding and knowledge regarding the quality of coffee beans produced by Muara Betung Village residents and how to overcome obstacles that will arise during the coffee bean harvesting and drying process. In this activity, direct assistance was provided to the community starting from direct introduction to the equipment that will be used for post-harvest handling, the coffee picking process by selecting coffee beans and taking ripe coffee beans from the tree which is done by picking all the fruit at once and picking ripe fruit one by one. After that, the process of drying the residents' coffee beans is carried out to produce good quality by utilizing the yard or on the side of the road with a sack or tarpaulin base. The drying process by utilizing the heat of sunlight will be able to maintain the cleanliness of the coffee and can be monitored direction.